The Relationship Between Dividend Payments And Firm Performance: A Study Of Listed Companies In Morocco - Rachid M’rabet; Wiame Boujjat (European Scientific Journal, ESJ, 2016)
Many theories have been documented on the relevance and irrelevance of dividend policy. Authors continue to come up with various conclusions with regard to dividend policy from their empirical studies. This paper sought to examine the relationship between dividend policies and financial performance of selected listed firms in Morocco. Data were sourced through secondary means from the annual reports of the sampled quoted firms and was analyzed using panel data regression model. Two models were developed in an attempt to provide a theoretical explanation on the birds-in-hand dividend relevance theory and the Modigliani and Miller’s (MM) dividend irrelevance theory. The findings indicated that Dividend policy is an important factor affecting firm performance. Their relationship was also strong and positive. This therefore showed that dividend policy was relevant. It can be concluded, based on the findings of this research that dividend policy is relevant and that managers should devote adequate time in designing a dividend policy that will enhance firm performance and therefore shareholder value. Management of companies should also invest in projects that give positive Net Present Values, thereby generating huge earnings, which can be partly used to pay dividends to their equity shareholders.